Impact of Maximal Cytoreductive Surgery plus Regional Heated Intra-peritoneal Chemotherapy (HIPEC) on Outcome of Patients with Peritoneal Carcinomatosis of Gastric Origin: results of the GYMSSA Trial - Rudloff, Udo (J Surg Oncol, 2014)
BACKGROUND: A prospective randomized trial was conducted to compare the impact of systemic chemotherapy vs. multi-modality therapy (complete cytoreductive surgery (CRS), hyperthermic intraperitoneal chemotherapy (HIPEC), and systemic chemotherapy) on overall survival (OS) in patients with gastric carcinomatosis. METHODS: Patients with measurable metastatic gastric adenocarcinoma involving the peritoneum, and resectable to ‘no evidence of disease’ were randomized to gastrectomy, metastasectomy, HIPEC, and systemic FOLFOXIRI (GYMS arm) or FOLFOXIRI alone (SA arm). RESULTS: Seventeen patients were enrolled (16 evaluable); 7 of 9 patients in the multi-modality GYMS arm achieved complete cytoreduction (CCR0). Median OS was 11.3 months in the GYMS arm and 4.3 months in the SA arm. Four patients in the GYMS arm survived >12 months, 2 patients close to 2 years at last follow-up, and 1 patient more than 4 years, with 2 of these patients still alive. No patient in the SA arm lived beyond 11 months. All patients surviving beyond 12 months in the surgery arm achieved complete cytoreduction and had an initial Peritoneal Cancer Index (PCI) of ≤15. CONCLUSION: Maximal cytoreductive surgery combined with regional (HIPEC) and systemic chemotherapy in selected patients with gastric carcinomatosis and limited disease burden can achieve prolonged survival.